A mechanistic perspective for airfield pavements evaluation focusing on the asphalt layers' behaviour. Issue 14 (6th December 2022) - Gkyrtis, Konstantinos; Armeni, Angeliki; Loizos, Andreas
ABSTRACT: The preservation of structurally sound airfield pavements is critical for the capacity of the air transportation network. As a standard practice, the design and evaluation of flexible airfield pavements are mainly based on the Multi-Layered Elastic Theory (MLET) in accordance with the Federal Aviation Administration (FAA) principles. However, Asphalt Concrete (AC) materials perform as temperature- and loading rate-dependent materials because of the viscous nature of asphalt binders. This in conjunction with the real moving loading conditions imply that the pavement analysis and evaluation outcome might be significantly different from what is assessed according to MLET. The research is concentrated on adopting a mechanistic framework for the assessment of airfield pavements considering both assumptions for AC material characterisation (i.e. elastic and viscoelastic). AC viscoelasticity is accounted as per the MEPDG suggestion for in-service pavements and an energy-based damage evaluation is performed based on the FAA recommendations. A thorough field experiment along an airfield runway pavement, including sample coring and non-destructive data, is organised to meet the research aim. Results demonstrate an applicable approach that seems to be conservative when AC is considered as a viscoelastic material. This is expected to profoundly affect the decision-making when managing airfield pavement infrastructure.